Changes in the bacterial and microeukaryotic communities in the bioreactor upon increasing heavy metal concentrations - Aceves-Suriano, Claudia E.; Montoya-Ciriaco, Nina; Hernández-Guzmán, Mario; Hernández-Martínez, Gabriel R.; Navarro-Noya, Yendi E.; Thalasso, Frédéric; Dendooven, Luc (Frontiers in Environmental Chemistry, 2023)
Heavy metals are necessary at low concentration for biological activity, but they are often toxic for microorganisms at high concentrations. Amplicon sequencing of 16S rRNA and 18S rRNA was used to investigate changes in the bacterial and microeukaryotic communities in an activated sludge bioreactor incrementally contaminated with nickel (Ni), copper (Cu), and zinc (Zn) with an IC50 value ranging from 0% to 100%, as previously determined, while an uncontaminated bioreactor served as a control. The chemical oxygen demand (COD) was on average 90% in the uncontaminated bioreactor but dropped to 49% when the heavy metal concentration was 100% IC50. The bacterial community in the uncontaminated bioreactor was dominated by Alphaproteobacteria (mostly Agrobacterium and Brevundimonas) when the heavy metal concentrations were low and Bacteroidetes (mostly Sphingobacterium) when the highest amounts of heavy metal concentrations were applied. The members of Ciliophora, Ascomycota, and Basidiomycota alternatively dominated in the uncontaminated bioreactor, while Ascomycota (mostly Fusarium) dominated in the contaminated bioreactor. The results revealed that increased concentrations of Ni, Cu, and Zn altered the bacterial and microeukaryotic communities and some putative metabolic functions.